Pengaruh Pelaksanaan Famili Center Care : Kangaroo Mother Care (KMC) Terhadap Kecemasan Keluarga Pada Pasien Infant Yang Dirawat Di Ruang Nicu Rs Ibu Dan Anak Dwi Sari Lubuklinggau Tahun 2025 - Tsuraiya Indah Permata Sari; Tuti Rohani; Sulastri Sulastri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Caring for low birth weight (LBW) infants in the Neonatal Intensive Care Unit (NICU) often causes anxiety in families due to limited interaction, the infant's vulnerable condition, and the intensive care environment. One approach that can be used to address family anxiety is the implementation of Family Centered Care (FCC) through the Kangaroo Mother Care (KMC) method. This study aims to determine the effect of implementing Family Centered Care: Kangaroo Mother Care (KMC) on family anxiety in infant patients treated in the NICU of RSIA Dwi Sari Lubuklinggau in 2025. This study used a quasi-experimental design with pre-and post-tests. The population was 708, with 246 LBW cases and a sample size of 15. The research data were secondary data. Data analysis used the Wilcoxon test (a nonparametric test). The results showed that the average family anxiety level before KMC implementation was 20.20 and decreased to 8.47 after KMC implementation. The statistical test results showed a p-value of 0.001 (p ≤ 0.05), indicating a significant effect of the implementation of Family Center Care Kangaroo Mother Care (KMC) on reducing family anxiety in infant patients in the NICU of RSIA Dwi Sari Lubuklinggau in 2025. The conclusion of this study is that the implementation of Family Center Care through the Kangaroo Mother Care (KMC) method is effective in reducing family anxiety in infant patients treated in the NICU. Therefore, KMC is recommended as a nursing intervention to improve the quality of neonatal nursing care and support family psychological well-being.